Tin‐Catalyzed Synthesis of 5‐Substituted 1H‐Tetrazoles from Nitriles: Homogeneous and Heterogeneous Procedures. Issue 4 (20th December 2018) - Chrétien, Jean‐Mathieu; Kerric, Gaelle; Zammattio, Françoise; Galland, Nicolas; Paris, Michael; Quintard, Jean‐Paul; Le Grognec, Erwan
Abstract: The preparation of 5‐substituted 1H‐tetrazoles was efficiently achieved by reaction of trimethylsilylazide with nitriles using a triorganotin alkoxide precatalyst. The reaction mechanism was first investigated using a homogeneous tributyltin derivative and was explored through experimental investigations and DFT calculations. A heterogeneous version was then developed using a polymer‐supported organotin alkoxide and afforded an efficient method for the preparation of tetrazoles in high yields with an easy work‐up and a residual tin concentration in the desired products compatible for pharmaceutical applications (less than 10 ppm). Abstract :